Shifting Borders and Shifting Identities: Ethnic Conflicts and the Construction of Otherness in Polish-Ukrainian Relations from the 17th Century to the 20th Century - Zhang, Ningxi (Mundus Slavicus I, 2025)
This study examines the shifting borders and identities in Polish-Ukrainian relations from the 17th to the 20th century, focusing on the construction of Otherness. Through an analysis of historical events and literature, particularly Sienkiewicz’s With Fire and Sword and Gogol’s Taras Bulba, it explores how national identities were shaped by conflict and territorial changes. The research highlights the role of literature in perpetuating ethnic divisions and constructing cultural boundaries.